Defence of abatement for defective works [electronic resource] - 436645 Mohamad Fairuz Kiprawi; Fakulti Alam Bina (2009)
Thesis (Sarjana Sains (Pengurusan Kontrak pembinaan))- Universiti Teknologi Malaysia, 2009